Controllable construction of half-sandwich octanuclear complexes based on pyridyl-substituted ligands with conjugated centers12. Issue 25 (13th June 2017) - Guo, Bei-Bei; Lin, Yue-Jian; Jin, Guo-Xin
Abstract : Based on three tetradentate ligands with conjugated centers, seven half-sandwich octanuclear complexes were selectively obtained. Several subsequent structural conversions were also successfully conducted. Abstract : Functional metal bis(1, 3, 5-triazapentadienato) units [M(tap)2 ] (M = Ni II /Pd II ) and pyrene groups were introduced as central units of three tetradentate tetrapyridyl-substituted ligands, with which seven half-sandwich organometallic complexes were controllably synthesized. The multi-centered hybrid products constructed from the two [M(tap)2 ] units revealed delocalized π-bonding environments. The products were characterized by proton NMR and IR spectroscopy, elemental analyses and electrospray ionization (ESI) mass spectrometry. The molecular structures of four of the products were determined by X-ray diffraction analysis, revealing their octanuclear structures.